2003
DOI: 10.1046/j.1365-294x.2003.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of molecular evolution and diversification in a biodiversity hotspot: the California Floristic Province

Abstract: The California Floristic Province harbours more endemic plant and animal taxa and more identifiable subspecies than any other area of comparable size in North America. We present evidence that physical historical processes have resulted in congruent patterns of genetic diversity over the past 2-10 million years. Using a molecular clock approach we show that diversification and establishment of spatial genetic structure across six taxonomic groups coincide with the putative age of California's mountain ranges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
278
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(290 citation statements)
references
References 54 publications
11
278
1
Order By: Relevance
“…The San Andreas fault which opened up the proto Bay of California and originated the Baja peninsula began its work only 15 million years ago (Kumar, 2013). Both the Baja Peninsula and the American Southwest are heterogeneous in their topography, flora, and weather regimes that have led to high levels of endemism and diversity (Hopkins, 2014;Kumar, 2013;McLaughlin, 1986;1989;Calsbeek et al, 2003). In addition to the geologic forces upon the landscape, alternating wet and dry periods, and more recently cold and hot oscillations, have resulted in present day deserts interspersed with mountains, canyons, relic watersheds, playas, alluvial fans, eolian dune fields, as well as plant-stabilized dunes, (http://pubs.usgs.gov/of/2004/1007/geologic.html, and citations therein) all of which are inhabited by Arenivaga.…”
Section: Resultsmentioning
confidence: 99%
“…The San Andreas fault which opened up the proto Bay of California and originated the Baja peninsula began its work only 15 million years ago (Kumar, 2013). Both the Baja Peninsula and the American Southwest are heterogeneous in their topography, flora, and weather regimes that have led to high levels of endemism and diversity (Hopkins, 2014;Kumar, 2013;McLaughlin, 1986;1989;Calsbeek et al, 2003). In addition to the geologic forces upon the landscape, alternating wet and dry periods, and more recently cold and hot oscillations, have resulted in present day deserts interspersed with mountains, canyons, relic watersheds, playas, alluvial fans, eolian dune fields, as well as plant-stabilized dunes, (http://pubs.usgs.gov/of/2004/1007/geologic.html, and citations therein) all of which are inhabited by Arenivaga.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, multiple studies have shown higher levels of phylogeographic differentiation in California than in the Pacific Northwest, where populations of many species became established only after the retreat of Pleistocene glaciers (26,36,37). Recent comparative analyses have indicated that patterns of molecular differentiation within many California taxa coincide with geographic barriers, such as those created by the Transverse Range, the Monterey Bay, and the Los Angeles Basin (25,26). Together, these studies indicate that such phylogeographic structure evolves over time due in part to reduction of gene flow across geographic barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Collection sites ranged in elevation from 30 to 2,010 m above sea level, representing a broad range of habitats and rock substrates. The sites spanned the major common phylogeographic breaks that have been found in molecular studies of a wide range of taxa within this region (25,26). We also analyzed leaves of two G. ovalis and two P. gardneri individuals to use as outgroups in clustering analyses.…”
Section: Distribution Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each species has undergone processes such as vicariance, dispersal, population bottlenecks, etc., as a result of historical changes in the environment, including orogeny, volcanism, soil genesis, and climatic events such as glaciation. Some ecosystems currently span geographic regions that have differed greatly in the environmental upheavals that have occurred, resulting in great spatial differences in genetic architecture and species diversity (Demesure et al1996;Soltis et al 1997;Avise 2000;Taberlet and Cheddadi 2002;Calsbeek et al 2003).…”
Section: Introductionmentioning
confidence: 99%